2019
DOI: 10.1002/aenm.201901863
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Engineering Enhances the Performance of Mixed‐Cation Perovskite Materials for Indoor Photovoltaic Applications

Abstract: Indoor photovoltaics (IPVs) are attracting renewed interest because they can provide sustainable energy through the recycling of photon energy from household lighting facilities. Herein, the Shockley–Queisser model is used to calculate the upper limits of the power conversion efficiencies (PCEs) of perovskite solar cells (PeSCs) for two types of artificial light sources: fluorescent tubes (FTs) and white light–emitting diodes (WLEDs). An unusual zone is found in which the dependence of the PCEs on the bandgap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 37 publications
2
72
0
Order By: Relevance
“…Figure 5 b shows the corresponding time-resolved PL (TRPL) decay profiles for the PeLEDs prepared under various conditions. The curves could be fitted well using a biexponential decay equation [ 27 , 28 ]. The fast decay (τ 1 ) could be assigned to the surface recombination, while the slower decay (τ 2 ) represents radiative recombination [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 b shows the corresponding time-resolved PL (TRPL) decay profiles for the PeLEDs prepared under various conditions. The curves could be fitted well using a biexponential decay equation [ 27 , 28 ]. The fast decay (τ 1 ) could be assigned to the surface recombination, while the slower decay (τ 2 ) represents radiative recombination [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The adjusting stoichiometric ratio of halide ions or using triple cations may bring about the possibility of better PSC performance as a result of a closer bandgap to 1.9 eV. Accordingly, Br − ions were added into the PSCs to increase their bandgap values by Wu et al They demonstrated the bandgap of MA 0.85 Cs 0.15 Pb(I 0.85 Br 0.15 ) 3 can be enlarged to 1.66 eV, which resulted in the highest PCEs of 25.94% and 25.12% under illumination from fluorescent tubes and a white LED 76 . Similarly, Cheng et al reported a triple‐anion CH 3 NH 3 PbI 2−x BrCl x PSCs with a specially tailored bandgap.…”
Section: The Development Of Photovoltaics For Indoor Applicationmentioning
confidence: 99%
“…Wu et al reported that the perovskite bandgap increased with the addition of Br − ions into common perovskite materials, achieving an bandgap energy of 1.66 eV for efficiently harvesting photonic power from the indoor lighting sources. [ 70 ] In addition, Choi et al identified that Cs + cations can significantly improve the stability and efficiency of PSCs. [ 71 ] Therefore, the addition of Br − ions to mixed cationic perovskites is an effective approach for improving the bandgap and device performance.…”
Section: Advances In Indoor Photovoltaicsmentioning
confidence: 99%